Values as Phenomena of Truth: The Mythopoetic Aesthetics of Thought as Highest Act - Shchepanovskaya, Siyana Vitalievna (Cultural Arts Research and Development, 2026)
This theoretical-philosophical investigation proposes a synthesis of mythopoetic, phenomenological, and ethical discourses to reconceptualize value-formation. It posits that the “Other” (alterity) operates in a dual capacity: as the radical unknown challenging the Self, and as the elevated dimension within communication where the trace of the ideal or the Divine is perceived. Central to this framework is a critical distinction between three modalities of myth. “Mythopoesis” is defined as the artistic-aesthetic act where thought, expressed in language, becomes immediate action, with the author creatively immersed in the “sea” of the mythopoetic as an elemental force. “Myth-creation” signifies the subject’s Heideggerian openness to myth’s content and form through the encounter with the creative Other, facilitating access to the depths of the self. “Myth-making,” in turn, is treated as the most formal and external approach, characteristic of certain rationalizing discourses that map myth from a distance. The article argues that a holistic understanding requires integrating these modalities. By embracing the original concept of the already nonreflective—a post-Hegelian stage of consciousness that overcomes pure intellective reflection to consciously readmit myth as the awakened elemental energy of reason itself—this project seeks to restore the vital fabric of life and stimulate the “high passions” essential for ethical engagement, arguing that such restoration occurs through the mythopoetic act.